A Case of Glucocorticoid Remediable Aldosteronism and Thoracoabdominal Aneurysms. (5th June 2016) - Shahrrava, Anahita; Moinuddin, Sunnan; Boddu, Prajwal; Shah, Rohan
Abstract : Glucocorticoid remediable aldosteronism (GRA) is rare familial form of primary aldosteronism characterized by a normalization of hypertension with the administration of glucocorticoids. We present a case of GRA and thoracoabdominal aneurysm complicated by multiple aortic dissections requiring complex surgical and endovascular repairs. Registry studies have shown a high rate of intracranial aneurysms in GRA patients with high case fatality rates. The association of thoracoabdominal aneurysms with GRA has not been described, thus far, in literature. Studies have shown that high tissue aldosterone levels concomitant with salt intake have a significant role in the pathogenesis of aneurysms and this may explain the formation of aneurysms in the intracranial vasculature and aorta. The association of GRA with thoracic aortic aneurysms needs to be further studied to develop screening recommendations for early identification and optimal treatment. Also, the early use of mineralocorticoid antagonists may have a significant preventive and attenuating effect in aneurysm formation, an association which needs to be confirmed in future studies.